The Analysis of Concepts Comprehension in Scie nce Subject Matter of the Fourth Grade Students in Group II Banjar Sub- district - Widiawati, Ni Putu (Universitas Pendidikan Ganesha, 2017)
This study was aimed at describing students? concept knowledge in science. Three elementary schools around cluster II in Banjar subdistrict such as SD Negeri 1 Temukus, SD Negeri 4 Temukus, and SD Negeri 5 Temukus were used as the sites of this study. The subject of this study was fourth grade students and elementary teachers in each school, while the object was students? concept knowledge in science, the activities conducted to improve their comprehension, and the obstacles faced by students. The data of students? science concept knowledge were collected through tests and interview. The result of this study showed that 10.81% of students got the average scores from the test, around 45.95% of students got low scores, and around 43.24% of students got high scores. Meanwhile, the result of indicator analysis pointed on the highest category (around 88.92%) from indicator of giving example and the lowest category from indicator of explaining (60.81%). Based on the result of interview, it was known that the activities conducted to improve students? concept knowledge in science were by doing learning activities which students were interested with such as group discussion, project, observation, and experiment. It was also known that the students faced some obstacles in comprehending the concept such as low motivation of students, inadequate of learning facilities, and less interesting learning methods used.